Fault section detection and location on distribution network using analytical voltage sags database - Khalid, A.R.; Mokhlis, Hazlie; Li, H. (2006)
This paper presents the application of voltage sags information for automatic fault section detection and location on a distribution network. Based on a network topology and load estimations obtained from load modeling, this method uses a three phase load flow and fault analysis to establish analytical voltage sags database information for a studied distribution network. The database contains voltage sag magnitude and phase shift information of simulated fault for all nodes on the distribution network. When a fault occurs in the network, voltage sags at the monitored bus is compared to the voltage sags in the database. By doing this all the possible sections due to the fault can be selected. Finally, the most probable faulty section is identified using probability approach.This paper presents the implemented algorithms and the test of the algorithms on typical distribution networks. The obtained results prove the capability of the approach in locating fault section.